Totalitarianism Between Ideology and Theory - Dobeš, Jan (Dějiny – teorie – kritika, 2007)
This study deals with the idea and the conception of totalitarianism. It chronicles the development of the term from its first use in the 1920s to its gradually widening scope, all the way up to its formulation as a consolidated concept after WWII. It contains at its basis the conviction that totalitarianism is a unique form of political power, to be distinguished from democracy and traditional dictatorships. Soon after this conception of totalitarianism was introduced, it encountered sharp criticism aimed at its inability to embrace the changes that occurred in communist states following Stalin’s death, subjected as they were to political interests and the logic of the Cold War and the belittling of Nazi crimes implicit in the comparison between Nazism and communism. However, in the 1980s – and particularly after 1989 – the theory of totalitarianism underwent a notable renaissance. In addition to its historical aspects, studies have concentrated on several competing theories meant to transform the concept or even completely supersede it (theories regarding authoritarian regimes, Fascism and political religion). In conclusion, the author points out that from its beginnings, the theory of totalitarianism has straddled the boundaries between ideology and politics on the one hand and ideology and science on the other.